Stable Isotopic Tracer Phospholipidomics Reveals Contributions of Key Phospholipid Biosynthetic Pathways to Low Hepatocyte Phosphatidylcholine to Phosphatidylethanolamine Ratio Induced by Free Fatty Acids - Peng, Kang-Yu; Barlow, Christopher K; Kammoun, Helene; Mellett, Natalie A; Weir, Jacquelyn M; Murphy, Andrew J; Febbraio, Mark A; Meikle, Peter J (Metabolites, 2021)
There is a strong association between hepatocyte phospholipid homeostasis and non-alcoholic fatty liver disease (NAFLD). The phosphatidylcholine to phosphatidylethanolamine ratio (PC/PE) often draws special attention as genetic and dietary disruptions to this ratio can provoke steatohepatitis and other signs of NAFLD. Here we demonstrated that excessive free fatty acid (1:2 mixture of palmitic and oleic acid) alone was able to significantly lower the phosphatidylcholine to phosphatidylethanolamine ratio, along with substantial alterations to phospholipid composition in rat hepatocytes. This involved both a decrease in hepatocyte phosphatidylcholine (less prominent) and an increase in phosphatidylethanolamine, with the latter contributing more to the lowered ratio. Stable isotopic tracer phospholipidomic analysis revealed several previously unidentified changes that were triggered by excessive free fatty acid. Importantly, the enhanced cytidine diphosphate (CDP)-ethanolamine pathway activity appeared to be driven by the increased supply of preferred fatty acid substrates. By contrast, the phosphatidylethanolamine N-methyl transferase (PEMT) pathway was restricted by low endogenous methionine and consequently low S-adenosylmethionine, which resulted in a concomitant decrease in phosphatidylcholine and accumulation of phosphatidylethanolamine. Overall, our study identified several previously unreported links in the relationship between hepatocyte free fatty acid overload, phospholipid homeostasis, and the development of NAFLD.